The Ideal Regulation of Meaningful Public Participation In The Legislative Process By The House of Representatives - Lalu Muhammad Amar Fawazi; Ngesti Prasetyo; Riana Susmayanti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
Public participation in the formation of laws is one manifestation of the principles of popular sovereignty and a democratic state based on the rule of law. The development of Indonesian constitutional law, through Constitutional Court Decision Number 91/PUU-XVIII/2020, has introduced the concept of meaningful participation as a constitutional standard in the formation of laws. This concept requires the fulfillment of three main elements: the right to be heard, the right to be considered, and the right to be explained. However, the regulation of public participation in Article 96 of Law Number 13 of 2022 concerning the Formation of Legislation has not fully accommodated these three elements, particularly regarding the obligation of lawmakers to provide explanations for the follow-up of public input. This study aims to analyze the conformity of the regulation of public participation in the formation of laws with the constitutional standard of meaningful participation and formulate a reconstruction of the ideal regulation in the Indonesian legislative system. This study uses a normative legal research method with a legislative approach and a conceptual approach. Legal materials were obtained through a literature study consisting of primary, secondary, and tertiary legal materials, then analyzed prescriptively using Philippe Nonet and Philip Selznick's Responsive Legal Theory and Sherry R. Arnstein's Ladder of Participation Theory. The results of the study indicate that the current regulations have accommodated the right to be heard and some elements of the right to be considered through various public participation mechanisms. However, the right to be explained element has not received adequate normative guarantees because it is still facultative. Therefore, regulatory reconstruction is needed through changes to imperative norms, strengthening mechanisms for considering public aspirations, establishing a transparent feedback system, and increasing legislative accountability in order to realize meaningful public participation in the formation of laws.